CUMULATIVE LEGAL CLASSIFICATION OF AN ACT VERSUS ELIMINATIVE CONVERGENCE OF STATUTORY PROVISIONS - Emil W. Pływaczewski; Ewa Guzik-Makaruk (Probacja)
Authors decided to raise the problem of assessing the cumulative legal qualification of an act, which directly affects the punishment imposed on the perpetrator and, consequently, influences enforcement aspects, including the imposed probation measures. The scientific discourse is conducted on the basis of the background of the previously applicable construction of the elimination of the provisions of the Act. The dogmatic method, case law analysis and desk research were used in the study. Both approximate structures in the form of cumulative legal classification of an act and the eliminative confluence of provisions of the act have their advantages and disadvantages. However, it is impossible not to notice that the use of the cumulative legal classification of an offense in the practice of justice, which has been in force for almost 55 years, has a significant impact on limiting the courts' ability to apply each of the catalog of probation measures provided for by the applicable Penal Code. The strict penal policy, resulting indirectly from the use of cumulative legal classification of the act, undoubtedly affects the level of repression, which effects in a high rate of prisonization in Poland, especially compared to the European Union countries.